Perancangan Narasi Visual Sejarah Kawasan Laut Sulawesi Abad 19 - mega iranti kusumawardhani; Muhammad Cahya Mulya Daulay; Christian Aditya (ULTIMART Jurnal Komunikasi Visual, 2018)
This paper explains the process of constructing visual narration history of 19th century Sulawesi Sea region. It is visualized through storyboard and animatic, as a guidance for short animated film. it is focused on selecting process of the history content and how to visualize it. Literature studies, observasion and interpretation is chosen as the main method of the research. The result is a sequence of event which visualized through storyboard and animatic. Keywords: visual narration, history, Sulawesi Sea, storyboard